Changes in Subjective Well-Being in Timor-Leste on the Path to Independence - Richter, Kaspar (2012)
In countries emerging from ethnic and civil conflict, standard approaches to measuring trends in well-being do not account for the empowerment of the population due to the political liberalization, which is critical for the successful implementation of zero-generation reforms. They also fail to do justice to the often massive population displacement unleashed by the violence which makes a comparison of living standards from before to after the conflict problematic. Using the example of Timor-Leste, this paper demonstrates how subjective, objective, and recall information collected through a cross-sectional household survey can be combined to provide a rich profile of trends in well-being from the pre- to post-conflict stage. By differencing across pre- and post-conflict periods, the regression estimates are robust with regard to psychological attributes or other time-invariant personal traits. The analysis shows that the changes in self-rated welfare and power in Timor-Leste broadly corresponded to changes recorded by objective indicators of economic resources, economic shocks, and ethno-linguistic status.